2006
DOI: 10.1354/vp.43-2-186
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Rhabdomyosarcoma in a Dog

Abstract: Abstract.A 10-year-old, female, mongrel showed hemorrhage from vulva. By magnetic resonance image (MRI) and endoscopic examination, a multipapillary mass with a grape-like appearance was found around the urethral opening. Histologically, the mass consisted of variable-sized round-, spindleto-polygonal-shaped tumor cells including many multinuclear cells. Mitotic figures were also frequently observed. In some areas, that tumor cells were loosely arranged, with intercellular myxoid components. Immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Similar to humans, the majority of rhabdomyosarcomas reported in dogs have occurred in tissues that normally do not contain striated-muscle cells, such as the pharynx, gingiva, urethra, trachea, larynx, and the jaw bone. 6,12,14 The reason that rhabdomyosarcomas arise in these sites is not clearly understood, but it is thought that myogenic transformation may be induced in non-muscle cells by a genetic problem, such as genetic lesions, related loss of heterozygosity, genetic fusions, or tumorigenic influences. 13 In the present case, the tumor occurred in the axillary region and involved striated muscles of the shoulder and thoracic limb.…”
Section: <!?Show "Fnote_aff1"$^!"content-markup(/author-grp[1]/aff|/author-grp[1]/dept-list)>mentioning
confidence: 99%
“…Similar to humans, the majority of rhabdomyosarcomas reported in dogs have occurred in tissues that normally do not contain striated-muscle cells, such as the pharynx, gingiva, urethra, trachea, larynx, and the jaw bone. 6,12,14 The reason that rhabdomyosarcomas arise in these sites is not clearly understood, but it is thought that myogenic transformation may be induced in non-muscle cells by a genetic problem, such as genetic lesions, related loss of heterozygosity, genetic fusions, or tumorigenic influences. 13 In the present case, the tumor occurred in the axillary region and involved striated muscles of the shoulder and thoracic limb.…”
Section: <!?Show "Fnote_aff1"$^!"content-markup(/author-grp[1]/aff|/author-grp[1]/dept-list)>mentioning
confidence: 99%
“…RMS is a tumor derived from skeletal muscle, composed of anaplastic muscle cells, and is one of the malignant neoplasms seen in veterinary medicine. According to the literature, the disease rarely affects domestic animals [8,17]. In dogs, the skeletal muscle of the tongue, larynx, myocardium and urinary bladder are the most common sites involved [2,10].…”
mentioning
confidence: 99%
“…According to the animal's owner, the lesion showed a rapid growth be corresponded to its invasive pattern. Once again, just few cases of RMS have been reported in dogs and the clinical behavior in each subtype is not well understood [8,17]. Besides, its poor prognosis may be also associated to the location of the tumor, which affected the central nervous system resulting in clinical disturbances.…”
mentioning
confidence: 99%
“…The immunohistochemical markers of skeletal muscle such as vimentin, desmin, myoglobin and myogenin play a critical role in differential diagnosis of rhabdomyosarcoma (Dias et al 2000;Suzuki et al 2006). To the authors' knowledge, in dogs, four cases of alveolar rhabdomyosarcoma (Seibold Sarnelli et al 1994;Kim et al 1996;Bae et al 2007) have been reported, which occurred in the gingiva, urinary bladder, genital tract, retroperitoneal cavity, left maxillary area and greater omentum, and these cases were confirmed via myoglobin immunohistochemistry.…”
Section: Discussionmentioning
confidence: 74%